PENGARUH SPIRITUALITAS, DISIPLIN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DIMEDIASI OLEH MOTIVASI KERJA - Ilham Tahier; Prasetiani Gautama; Muchtar Surullah (Kelola: Journal of Islamic Education Management, 2022)
The purpose of this study was to determine the effect of spirituality, and work discipline on the Organizational Citizenship Behavior of teachers at SMPN 2 and SMPN 3 Cilaku which was mediated by work motivation. The distribution of questionnaires using primary data and using an explanatory research design to determine the relationship between several variables. Respondents in this study were all teachers who teach at SMPN 2 and SMPN 3 Cilaku with saturated samples, by distributing questionnaires. The analysis used is multiple linear regression with SPSS and SEM PLS applications. Data analysis shows that spirituality and work discipline has a positive and significant effect on the work motivation of teachers at SMPN 2 and SMPN 3 Cilaku directly. Spirituality has a direct effect on Organizational Citizenship Behavior, while work discipline has no direct effect on Organizational Citizenship Behavior. Likewise, work motivation does not significantly affect Organizational Citizenship Behavior directly. Indirectly, both spirituality and work discipline has no effect on Organizational Citizenship Behavior through work motivation for all teachers at SMPN 2 and SMPN 3 Cilaku.